the Role Of Physical And Sports Activities In Developing Socialization For High School Students (15-18 Years - Derragui , Yassine; Laloui , Abdelhafid (sports creativity, 2025)
The objective of our study is to depict the role of physical and sports activities in developing socialization, and to know to what extent the educational system has contributed in realizing it through its various effective institutions and established programmes. We have used the descriptive approach in our study ; and to collect data, we depended on the questionnaire to monitor the various indicators which was field applied on an arbitrary sample of 70 first year students , boys and girls , at the level of secondary schools in Ras El Oued , BBA . After viewing and analyzing the data , using the )spss(, we found out the sports and physical activities contributes in the social interaction of teenagers at the secondary level through integrating them in a group and instilling the values of cooperation and solidarity among them . They also impact positively the psychological status of secondary school adolescents, and take part in forming awareness about the importance of practicing physical and sports activities for their psychological health